2017
DOI: 10.1007/s10068-017-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential abilities of Korean soybean varieties to biosynthesize glyceollins by biotic and abiotic elicitors

Abstract: Glyceollins synthesized in soybeans that are exposed to biotic or abiotic stress have been reported to have health benefits. Considering that glyceollins are synthesized from daidzein via several enzymatic steps and that isoflavone concentration widely varies among soybean varieties, the abilities of 60 soybean cultivars to synthesize glyceollins were compared under different elicitation conditions. Soybeans accumulated glyceollins differentially depending upon the cultivar when elicited with. Contrary to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This compound can open the metabolic process of enzymatic activity, which can increase the content of secondary metabolites and sometimes even induce new compounds. Elicitors can be classified as biological and abiotic elicitors, depending on their sources (Park et al 2017). Dong et al (2010) revealed that 6.25-22.25 mg/L salicylic acid (SA) could elicit the accumulation of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This compound can open the metabolic process of enzymatic activity, which can increase the content of secondary metabolites and sometimes even induce new compounds. Elicitors can be classified as biological and abiotic elicitors, depending on their sources (Park et al 2017). Dong et al (2010) revealed that 6.25-22.25 mg/L salicylic acid (SA) could elicit the accumulation of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among eight different fungal strains evaluated for their ability to activate glyceollin synthesis, it was observed that the NRRL 3653 strain of Trichoderma reesei was able to cause glyceollin accumulation in soybean cotyledons to reach 3.763 mg/g [ 163 ]. Evaluation of the synthesis ability of 60 different soybean varieties under various conditions revealed that treatment with Aspergillus sojae resulted in the highest yield of glyceollin, exceeding 8 mg/g [ 164 ]. Under acidic conditions (pH 3.0), glyceollin synthesis was effectively promoted [ 165 ].…”
Section: Elicitors and Transcription Factors That Regulate Glyceollin...mentioning
confidence: 99%
“…Glyceollins, including glyceollin I, II and III (GI, GII and GIII), are the most important phytoalexins present in soybeans exposed to certain fungi and some abiotic elicitors [5,6]. They serve as a protective system in plants through their antibacterial, antifungal and antinematode actions [7].…”
Section: Introductionmentioning
confidence: 99%